DEVELOPMENT OF STUDENT WORKSHEET "INOKREAT" BASED INQUIRY ON PRACTICUM IMPACT OF CIGARETTE ON HEALTH - Munadhiroh, Siti; Lisdiana, Lisdiana (Journal of Biology Education, 2017)
This Study aims to analyze the validity and effectiveness of ?inokreat? LKS based on inquiry on the impact of smoking on health. This research is designed as Research and Development (R & D) research consisting of 10 stages: potential and problem stage through questionnaire and interview method, data collection phase, LKS product design, LKS design validation by expert to test the validity of LKS, revision phase I, small scale in 10 random class VIII students, second phase revision, large-scale trial in one class VIII with 29 students to analyze the effectiveness of LKS on learning, product revision, and finished product. Expert judgment result on LKS "inokreat" based on inquiry on the impact of cigarette on health shows that LKS of valid development result is used in learning with percentage of material feasibility aspect 85% and media feasibility aspect 97,2% with criteria very feasible. The results of large-scale trials show that LKS "inokreat" is effective against students' learning outcomes with an average NGain score of 0.61 indicating an increase in learning outcomes from pretest to posttest in moderate categories. The average completeness of the classical students reached 89.65%. The average percentage of practicum skills was 88.5% and the presentation skills were 87.85% with very good category and the average of student discussion activity was 75.7% with the active category and the students' responses were 74.8% with the agreed category.